Esplícitos engodos - Desejo e erotismo na ausência do corpo - Scoz, Murilo (2006)
The present research examines the construction of the erotic message in advertising images which do not show bodies and do not bring an authentic subjectivity. If an absence is configured, the image, that still has sexual effects, seems to do it through clues of an absent simulacrum, through references to sexual elements, or through a simulated simulacrum. When there s an authentic body on the image (a top model, for instance), enunciation works between subjects through a process that implies the enunciation subject the consumer as the enunciate subject s object. This recognition process is reciprocal and based on presence, depending on the erotic values of the presented bodies. This research investigates the construction of erotic simulacrum when there s no body, and how speech syntax applies sexual connotation to products. The hypotheses pointed in this study take advertising as a dynamic language, with substantial references from other systems, like scenic arts, painting and photography, although with major specificities that configure a unique theme. The epistemological base of this work is the discursive semiotics, and its fundamental bibliography comes from social semiotics, developed by E. Landowski, psychology of perception, mass communication theories, advertisement researches, and others theoretical perspectives. In order to show how the erotic simulacrum is built without the figuration of the body, this study analyses ad pictures from national and international magazines. The 110 selected ads allowed a comprehension of the eroticism construction in advertisement when the body is omitted, through clever references to corporeity, or through arbitrary constructions of an absent sexuality. This variation in the believability of simulacra implies differentiated interaction regimes, junction as much as union